(untitled) (Journal of Environmental Bioremediation and Toxicology, 2022)
Petroleum hydrocarbon-polluted environments contain massive diversity of microbes capable of transforming or reducing hydrocarbon concentrations, and this has consequently led to an interest in the cultivation screening for microbial potentials to remediate petroleum hydrocarbon-polluted lands. Conversely, the reliance singly on culturing approach for the discovery of various hydrocarbon-degrading bacteria without probing for its hydrocarbon degradative capabilities has now become rampant in some research communities, and in most cases may not be justifiable. Besides, vast microbial communities with hydrocarbon-degrading potentials are eluded with the conventional method. Opportunely, the advent of culture-independent approaches such as molecular techniques and next-generation sequencing (NGS) technology has shifted the paradigm of research, now focusing on contemporary and advanced trending ways to discover the uncultivable microbial communities and assess their functional roles in the environment. To ascertain that microorganisms cultured from polluted environmental samples are factual hydrocarbon-degrading strains, a microbiologist needs to investigate beyond just culturing and probe further for the hydrocarbon-degrading prowess by choosing from various arrays of the culture-independent approaches. Consequently, this counters the questionability of only the cultivation approach and explores the vast recompenses of the latter approach when coupled. This perspective review exposes the huge gap in the application of the lone conventional culturing technique for retrieving the uncultured communities, particularly the hydrocarbon-degrading group while hinting at complementary alternatives for improved research and scientific evidence-driven and justifiable study inference.